Hubungan Pemberian Makanan Tambahan dengan Variasi Menu terhadap Kenaikan Berat Badan pada Balita yang Berstatus Gizi Kurang - Meliana Eka Luwitasari; Nasriyah Nasriyah; Atun Wigati (Jurnal Syntax Admiration, 2024)
Stunting is a chronic nutritional problem caused by a lack of nutritional intake for a long time, especially in the first 1,000 days of a child's life. This malnutrition can interfere with the physical and brain growth of children, causing height that is not appropriate for age and various other symptoms such as a younger-looking face, delayed body growth, and impaired brain development. The purpose of this study is to determine the relationship between supplementary feeding and Menu Variation on weight gain in undernourished toddlers in Semirejo Village, Gembong District, Pati Regency. Method: The type of research used is quantitative research, which is a research method that uses research data in the form of numbers and analysis using statistics. Results: The results of the statistical test after combining the analysis results with chi square obtained a p value of 0.001 < 0.005, meaning that Ha was accepted and Ho was rejected, meaning that there was a relationship between providing additional food and menu variations to weight gain in toddlers with malnourished status. Conclusion: There was a significant relationship between supplemental feeding and menu variation on weight gain in undernourished toddlers with a p value of 0.001.